Optimalisasi Potensi Pariwisata melalui Rencana Tata Bangunan Lingkungan (RTBL) Kawasan Wisata Gunung Puntang, Kabupaten Bandung - Kurniawan, Mohd Ridho (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of the Gunung Puntang tourist area, Campakamulya Village, Bandung Regency, has high multispectrum potential, combining ecotourism, the history of the Malabar Radio Station (1917–1929), and Puntang Arabica Coffee agrotourism. However, the utilization of this potential is hampered by the absence of comprehensive planning documents, resulting in suboptimal management of objects and facility layout. This study aims to formulate spatial guidelines through the Building and Environmental Planning Plan (RTBL) to realize planned and sustainable development. The method used is qualitative-participatory (Participatory Mappingand FGD) adapted from the standard components of the RTBL. Data were analyzed using SWOT Analysis to formulate a development strategy. The research results in the form of an Eco-Heritage Edupark concept that divides the area into five functional zones: Education & History, Conservation & Adventure, Agrotourism, Commercial, and Residential. This RTBL provides planning guidelines for the revitalization of Malabar Station, improving accessibility, and increasing the capacity of local human resources. In conclusion, the preparation of the RTBL is a strategic step to create a superior destination with high competitiveness, while maintaining the balance of the local ecosystem and culture.